Project profitability analysis - Drenovac, Aleksandar Ž.; Drenovac, Bratislav Ž. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Numerous activities in modern business are performed through projects. Since projects are often very expensive, long-lasting, ans involve large amounts of assets and people for completing them, a decision about starting a project is to be based on measurable parameters.